Biological evaluation of enamel sealants in an organotypic model of the human gingiva - Zingler, Sebastian; Matthei, Byron Anton; Diercke, Katja; Frese, Cornelia; Ludwig, Björn; Kohl, Annette; Lux, Christopher J.; Erber, Ralf (Dental materials, 2014)
Objectives - Various sealant materials have been suggested to decrease decalcification during orthodontic treatment. However, only a few in vitro studies on the cytotoxicity of resinous pit and fissure sealants have been published, and to the best of our knowledge no similar studies are available for the enamel sealants used in orthodontics. Therefore, we aimed to characterize the possible adverse effects of enamel sealants, especially on the gingival epithelium. - Methods - Organotypic cultures of the human gingival mucosa were used to assess the possible impact of six enamel sealants. Differentiation and apoptosis were determined by immunofluorescent staining. The pro-inflammatory cytokines IL-1β and IL-6 were quantified by ELISA. Cytotoxicity was measured using MTS assays in monolayer cultures of human gingival fibroblasts. Leaching of monomers from enamel sealants was quantified using HPLC. - Results - The differentiation of the organotypic gingival mucosa remained unaffected. All under-cured and several standard-cured sealants (Light Bond™ Sealant, Light Bond™ Filled Sealant, and L.E.D. Pro Seal®) significantly induced apoptosis in the organotypic model. Light Bond™ Sealant, Light Bond™ Filled Sealant, and L.E.D. Pro Seal® caused a significant induction of pro-inflammatory cytokines. Reducing curing time had an influence on cytotoxicity in monolayer cultures of primary human oral cells. All resin-based sealants leached monomers. - Significance - Enamel sealants might exert adverse effects on the gingival epithelium. Due to the vicinity of the enamel sealant to the gingival epithelium, and the large surface area of applied sealants, these materials should be carefully applied and sufficiently cured.